FACTORS AFFECTING GRADE 11 STUDENTS’ ACHIEVEMENT IN LEARNING POPULATION EDUCATION IN SCHOOL POPULATION AWARENESS, INDONESIA - Andi Pancanugraha; Arisara Leksansern (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: School population awareness program (SSK) is a school program of teaching and learning strategies of population education developed at school level with the pilot project in Sukabumi, Indonesia. Prior this study, there was no research had been conducted to see the effectiveness of the program from the perspective of the students, on how the students perceived, their learning achievement, and whether the teaching and learning population under the SSK program contribute as the factor affecting learning achievement, which all of this could draw a conclusion whether the SSK program effective for students. Further, it would also give a valuable input for teacher and school sectors on how to improve the students’ learning achievement. This study has a purpose to investigate the attitude of student toward five aspect of learning situation of population education, which are the subject, method of teaching, activity of teaching, media of instruction, and class environment. Students’ learning achievement was also assessed in this study including the factors that affecting the students’ learning achievement in population education Methods: A descriptive cross-sectional study was applied using a quantitative research method. The sample size was 188 of eleventh grade students studying at three pilot projects of School Population Awareness in Sukabumi, Indonesia. Data were collected through a survey using close-ended questionnaire which distributed purposively.Results: Students’ attitudes were at high level, and their learning achievements were also high. Three predictive factors of learning achievement in population education were found: the attitude towards subject, activity of teaching, and method of teaching.Conclusion: From the result it was reveal that all of the predictive factors found were associated with the teaching and learning strategies of population education under the SSK program which draw a conclusion that the program is effective for the students. For BKKBN as the government institution who developed the SSK program it is recommends to advocate the Ministry of Education and Culture of Indonesia and other senior high schools to implement the SSK program based on the model of SSK implemented in Sukabumi. For the respective teachers and school sectors it is suggested to emphasize the students with the importance of learning population education, adding more real-life activities, and provide more group work in the learning process in order to improve the students’ learning achievement in population education.